Advancement of the assistance and support system for victims and witnesses of criminal offences – the role of civil society organizations in Croatia - Drožđan-Kranjčec Anamaria; Mamula Maja (Temida)
Legal and institutional framework of the system of support to victims of criminal offences as well as the significance of the Directive 2012/29/EU and its implementation in the legislation of the Republic of Croatia are elaborated in this paper. In addition, certain difficulties related to the victim support system in practice are identified. A new model of service provision to victims and witnesses of criminal offences through founding and active work of The Network of Support and Co-operation for Victims and Witnesses of Criminal Offences and its results after two years of work are presented. The role and importance of civil society organizations in this field are emphasized. The conclusion declares establishment of more quality system of assistance and support for victims and witnesses of criminal offences. A part of the system is supported institutionally through the activities within the Ministry of Justice and specially established departments within the courts. A part of support is ensured noninstitutionally through the work of The Network of Support and Co-operation for Victims and Witnesses of Criminal Offences. It is exactly that involvement of motivated, educated and dedicated civil society organizations turned out as a key factor in establishing the efficient system. We will be able to state that certain milestones are achieved after: 1) further development of the system as a whole which refers to amending and implementing the existing legislative framework, 2) establishing a larger number of departments within courts, 3) spreading the Network‘ s services to all counties in Croatia, and 4) strengthening capacity of organizations that are service providers. The key is to ensure the financial means for the Network‘ s activities, strengthening networking of all stakeholders and introducing systemical control of service provision quality for victims and witnesses on all levels.